Selenium-Modified Biochar Synergistically Achieves the Safe Use of Selenium and the Inhibition of Heavy Metal Cadmium - Wanjing Wang; Haiyan Jiang; Zebin Tan; Luyao Yu; Jie Chen; Qingliang Xiao; Qinlei Rong; Chunhuo Zhou (Molecules)
To address cadmium pollution in China’s cultivated land, chitosan, inorganic and organic selenium were used to modify rice husk charcoal for cadmium inhibition. Basic physicochemical properties of rice husk carbons were characterized (BET, FTIR, XRD, Zeta potential). Kinetic and isothermal adsorption experiments studied the adsorption of Cd2+ by modified biochar under different pH and dosages. A350 and C350 had pore changes, and B350 had a smoother surface. The polarity and Zeta potential of A350, B350, and C350 differed. B350 and C350’s kinetic adsorption fit the pseudo second order model, A350’s fit both the pseudo first and second order. Their isothermal adsorption fit Langmuir (B350, C350) and Freundlich (A350). Intraparticle diffusion was three-stage with single-layer chemical adsorption. The pH increase raised removal and adsorption of CK350, A350, B350, and C350. The dosage increase hiked removal but cut unit adsorption. A350 had the highest max adsorption (57.845 mg/g). All modifications enhanced Cd2+ adsorption, and the effect could be altered by adjusting pH and dosage.